Strategic collaboration between UMP and Agrico for Agricultural Development Qatar in Agricultural product development - UMP, PNC (2020)
Kuala Lumpur, January 20 - Universiti Malaysia Pahang (UMP) has ratified strategic cooperative ties with Agrico for Agricultural Development, Qatar (Agrico) which is a supplier for agricultural systems and greenhouse-grown produce in Doha, Qatar. UMP will work together with Agrico in research, product development, commercialisation, and expertise exchange for use in agriculture which will be utilised in Agrico’s greenhouses in Doha, Qatar.